Injuries of ductus thoracicus - І. D. Duzhyi; O. M. Lytvynenko; S. О. Holubnichyi; О. L. Sytnik; V. Ya. Pak; І. А. Symonenko (Клінічна хірургія)
Objective. To study peculiarities of course and diagnosis of traumatic and spontaneous injuries of ductus thoracicus.